2021
DOI: 10.3390/vaccines9080919
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Review of Immune Checkpoint Inhibitors in Advanced Clear Cell Renal Cell Carcinoma

Abstract: The use of checkpoint inhibitors in advanced and metastatic renal cell carcinomas (RCCs) has rapidly evolved over the past several years. While immune-oncology (IO) drug therapy has been successful at resulting in improved responses and survival, combination therapies with immune checkpoint inhibitors and vascular endothelial growth factor (VEGF) inhibitors have further improved outcomes. This article reviews the landmark trials that have led to the approval of IO therapies, including the Checkmate 214 trial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Interestingly, it has been demonstrated that G protein-coupled receptors (often overexpressed in HNC) ligands prostaglandin E2, bradykinin, and gastrin-releasing peptide activate EGFR signaling [ 125 , 126 , 127 ]. Another interesting therapeutic and prognostic target is the VEGF pathway (a member of the platelet-derived growth factor, PDGF, superfamily) [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], whose receptors are expressed both on endothelial cells and tumor cells and that include VEGF from A to E. VEGF (mainly VEGF-A) is often overexpressed in HNC and plays a key role as a mediator of angiogenesis, which supports tumorigenesis potentially modulating the tumor microenvironment [ 136 , 137 ]. On the other hand, hypoxia, one of the main components of the HNC microenvironment, is a major factor inducing VEGF expression through the expression of hypoxia-inducible factor-α (HIF-1α) [ 138 , 139 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…Interestingly, it has been demonstrated that G protein-coupled receptors (often overexpressed in HNC) ligands prostaglandin E2, bradykinin, and gastrin-releasing peptide activate EGFR signaling [ 125 , 126 , 127 ]. Another interesting therapeutic and prognostic target is the VEGF pathway (a member of the platelet-derived growth factor, PDGF, superfamily) [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], whose receptors are expressed both on endothelial cells and tumor cells and that include VEGF from A to E. VEGF (mainly VEGF-A) is often overexpressed in HNC and plays a key role as a mediator of angiogenesis, which supports tumorigenesis potentially modulating the tumor microenvironment [ 136 , 137 ]. On the other hand, hypoxia, one of the main components of the HNC microenvironment, is a major factor inducing VEGF expression through the expression of hypoxia-inducible factor-α (HIF-1α) [ 138 , 139 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…In recent years, researchers have found that targeted therapy combined with immunotherapy has beneficial treatment effects and good prospects in patients with advanced KIRC, and has shown a trend of gradually replacing targeted therapy alone (9). However, many patients do not benefit from the combined therapy because of the overlapping drug toxicity that affects their quality of life (10). Therefore, new molecular phenotypes should be established to divide the population more finely for the individualized selection of effective immunotherapy drugs or targeted drugs for patients with advanced or unresectable KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…Patient preferences may be influenced by several different variables, including treatment schedule, treatment-related toxicities, management options for these potential toxicities, and whether the approach would be covered by the patient’s insurance provider [ 34 , 35 ]. For instance, pembrolizumab can be given every 6 weeks as opposed to every 4 weeks with nivolumab therapy—making pembrolizumab a preferred drug for patients who face a distance barrier to accessing an infusion center.…”
Section: Current First Line Standard Of Carementioning
confidence: 99%